2015
DOI: 10.1007/s11067-015-9285-7
|View full text |Cite
|
Sign up to set email alerts
|

The Multiregional Core-periphery Model: The Role of the Spatial Topology

Abstract: We use the multiregional core-periphery model of the new economic geography to analyze and compare the agglomeration and dispersion forces shaping the location of economic activity for a continuum of network topologies characterized by their degree of centrality, and comprised between two extremes represented by the homogenous (ring) and the heterogeneous (star) configurations. Resorting to graph theory, we systematically extend the analytical tools and graphical representations of the coreperiphery model for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Additionally, the impact of the number of regions could depend on (or influence) the relative location of regions in space. This means studies which have focused on the role of space heterogeneity under a limited number of regions (e.g., Barbero and Zofío, 2016) may be complementary to our own.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the impact of the number of regions could depend on (or influence) the relative location of regions in space. This means studies which have focused on the role of space heterogeneity under a limited number of regions (e.g., Barbero and Zofío, 2016) may be complementary to our own.…”
Section: Resultsmentioning
confidence: 99%
“…Tabuchi and Thisse (2011) studied the rise of a hierarchical system of central places in a multi-location space. Barbero and Zofío (2016) considered different network topologies in order to study how the interplay between centripetal and centrifugal forces change according to the heterogeneity of location space. They showed that more heterogeneous configurations enforce the likelihood of agglomeration in regions with higher centrality; i.e., those that are relatively better located.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They use group theoretic bifurcation theory in order to obtain analytical results. However, these studies are also complemented by numerical simulations (see also Barbero & Zofío, 2016). In the present paper, we primarily present simulation results complemented by intuitive explanations of the underlying economic forces.…”
Section: Introductionmentioning
confidence: 95%
“…Based on New Geo-Economics and related research [27][28][29][30][31][32][33], we can also understand the spatial inconsistency of population distribution and economic development from the perspective of resource allocation. In regional economic development, the dominant powers over the allocation of resources include market mechanism and government mechanism.…”
Section: Determinants Of Cpementioning
confidence: 99%